VISUAL ARTS TEACHING METHODOLOGY AND PROBLEMS AND SOLUTIONS - Suyarov Nodirjon Toxirovich (Galaxy International Interdisciplinary Research Journal, 2023)
This article covers the problems and solutions in teaching fine arts and the methodology of teaching Fine Arts.